Beneficiamento de resíduo atmosférico de petróleo por destilação catalítica - Morais, Camila Gisele Damasceno Peixoto (2019)
The first step of oil refining is the atmospheric distillation in which a bottom product named atmospheric residue (AR) is formed. The retrieval of this residue is important, since there is an increasing global demand for petroleum. The catalytic distillation is a technique that combines component separation with reactivity process to obtain lighter derivatives such as gasoline and diesel. In this study, the AR was subjected to distillation under atmospheric pressure in its pure form (conventional) and with the addition of both HY zeolite and MCM-41 mesoporous material (catalytic). In order to characterize the AR, physical-chemical and rheological parameters were determined. The effectiveness of the processing was investigated through thermogravimetric analysis and gas chromatography. Kinetic parameters were calculated through kinetic model proposed by Flynn-Wall. The obtained results showed that the used residue can be classified as heavy, viscous and low pour point oil. Concerning the distillation curves, the addition of HY enabled a higher percentage of retrieval (50%), followed by pure residue (41%) and HY/MCM-41 mixture (25%). Furthermore, thermogravimetric data revealed two events of mass loss for AR, occurring between 100 and 390 ºC and 390 and 590 º C. Such events correspond to volatilization and thermal cracking, respectively. Three mass loss events for the distillates were revealed, being the first event the most evident one in the catalytic distillation with HY and occurring between 30 and 70 º C. A decrease of kinetic energy occurred in the reactions of thermal cracking of the distillates when compared to AR. Chromatogram analysis enabled both the identification of a higher yield of gasoline and kerosene for catalytic distillation using HY and majority production of heavy diesel and gasoil when HY/MCM-41 mixture was added as catalyst. In addition, residue distillation without catalyst produced more heavy gasoil and lubricating oil.